Dakwah dan Larangan Khutbah Jum’at Pada Masa Pandemi Covid 19 - Kusnadi; Asriadi (Prodi Sosiologi Agama, 2023)
This article discusses the impact of the COVID-19 pandemic on the implementation of Friday sermons at mosques in Indonesia. In this pandemic situation, the Indonesian government has issued a policy to limit religious activities as an effort to prevent the spread of the virus and to understand the efforts made by the government and religious institutions in dealing with this pandemic. The method used in this study is a qualitative descriptive method by conducting interviews with several religious leaders and social observers. The results of this study indicate that the COVID-19 pandemic has had a significant impact on the implementation of Friday preaching and sermons, due to the prohibition on large gatherings. Some of the views of scholars and guidelines in Islam which explain the unusual or compulsion of not doing Friday prayers so as to provide a petrified understanding of the tension of opinion among the general public. Therefore, the government and religious institutions are taking alternative steps such as carrying out Friday sermons virtually or through social media. Even so, several challenges still existed in the implementation of Friday sermons and sermons during the pandemic, including technical problems and limited internet access for the community. It is hoped that the results of this research can contribute to the development of Friday preaching and sermons during the COVID-19 pandemic